Motion Capture for the Masses - Staples, Joshua A.; Davis, Timothy A. (INFOCOMP Journal of Computer Science, 2006)
In this paper, we introduce a flexible and inexpensive means for acquiring motion capture data from a human actor or other object. The system described requires just a few pieces of hardware, while leveraging the capabilities of off-the-shelf software to track optical markers in raw film footage. The resulting data can then be applied to any virtual figure, as with motion capture data acquired by more traditional means.